Difference in Perception of Onset of Old Age in Traditional (Hadza) and Modern (Polish) Societies - Frąckowiak, Tomasz (Int J Environ Res Public Health, 2020)
Despite relatively clear physiological indicators of old age, little is known about cross-cultural differences in psychological perceptions of the transition to old age. Although recent studies suggest consistency between modern countries, the subjective perception of old age onset in traditional societies remains poorly explored. Therefore, we compared the perception of timing of old age between a traditional tribe of hunter-gatherers (the Hadza) and a Polish sample representing a modern, industrialized population. The results indicate that the Hadza perceive old age onset as being significantly earlier than do the Poles. Furthermore, we found between-gender differences in the Polish sample: men set a lower threshold of old age onset than women. The Hadza showed no between-gender difference. Although the samples were matched for age, a larger proportion of Hadza considered themselves old. We discuss these findings from cultural and demographical perspectives.